Effects of different Chinese traditional exercises on mental health during the COVID-19 pandemic: a systematic review and meta-analysis - Liu, Min; 张, 世晴; Zhao, Lijin (Frontiers in Public Health, 2024)
Introduction As the COVID-19 outbreak escalated into a global pandemic, there was a significant surge in mental health issues worldwide. Over the past three decades, traditional Chinese exercises (TCEs) has gained increasing recognition for its ability to regulate mental well-being. The aim of this study (PROSPERO CRD42024516002) was to comprehensively assess and carry out a meta-analysis on the impact of traditional Chinese exercise on personal mental well-being amidst the COVID-19 pandemic. Methods Literature with publication dates from 2020 to 2023 was searched in four databases, including CNKI, Wanfang, Pubmed and Web of science. The literature was selected layer by layer according to the PRIMA guidelines, and then the quality of the included literature was assessed using the Cochrane Risk assessment tool. Results A total of 174 articles were screened, and 10 studies met the criteria and were included in the study. The results showed that TCEs had a positive effect on anxiety symptoms [SMD = −1.68, I2 = 98.40, 95%CI = (−2.80, −0.56), p = 0.00] and depressive symptoms [SMD = -1.23, I2 = 89.23, 95%CI = (−1.87, −0.58), p = 0.00]. The data of subgroup analysis showed that Baduanjin exercise had the best effect on reducing anxiety [SMD = −2.29, I2 = 98.3, 95%CI = (−3.69, −0.89), p < 0.000]. Individuals who practiced TCEs less than or equal to 30 min each time had the best effect on anxiety [SMD = −2.06, I2 = 96.2%, p < 0.000] and depression [SMD = −1.90, I2 = 68.4, 95%CI = (−2.25, −1.55), p = 0.042]. Individuals who trained TCEs more than 7 times a week were most likely to reduce symptoms of anxiety [SMD = −4.30, I2 = 92.6, 95%CI = (−6.78, −1.81), p < 0.000] and depression [SMD = −2.39, I2 = 0.0, 95%CI = (−2.91, −1.87), p = 0.625]. It is worth noting that TCEs had the most significant effect on the improvement of depression in people aged 30–50 years [SMD = −1.58, I2 = 89.0, 95%CI = (−3.05, −0.10), p = 0.003]. Conclusion During the global pandemic, traditional Chinese sports have shown a positive and significant impact on reducing symptoms of anxiety and depression, and have played a significant role in improving mental health problems. Systematic review registration: PROSPERO, identifier CRD42024516002, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024516002.